Smart Control of Ship Propulsion System - Altosole, Marco; Acanfora, Maria; Balsamo, Flavio; Xing, Bowen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With the deep integration of cutting-edge technologies such as artificial intelligence, big data, and the Internet, ship propulsion control systems are also gradually undergoing a transformation from the mode of automatic control to intelligent control. In particular, the smart ship concept has become a key factor in the maritime industry's ambition to achieve sustainable green development. Currently, the development of all-electric propulsion and innovative hybrid ship propulsion systems is a priority, so that the efficiency of ship propulsion systems might be improved. Therefore, the aim of this monograph is to describe the intelligent control of ship propulsion systems. In this regard, this monograph deals with new approaches to the design of ship power systems. Among them, in terms of intelligent control, and using simulation experiments for comparison, the learning ability relied on by artificial intelligence is utilized to handle the collected data and generate corresponding commands, thus ensuring the safety and stability of the ship's movement. The main objective of this Special Issue is to fill existing knowledge gaps and provide additional ideas on the intelligent control of marine propulsion systems. Finally, we would like to express our deepest gratitude to the staff of MDPI Books and the editorial team of Marine Science and Engineering, especially the assistant editors of this Special Issue, the gifted authors, and the diligent and expert reviewers.